2020
DOI: 10.1007/s40670-020-01014-y
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Learning Versus Didactic Lecture in Teaching Bronchial Asthma for Undergraduate Medical Students: a Step Toward Improvement of Clinical Competencies

Abstract: Background Simulation-based learning (SBL), an effective teaching strategy, is still questionable on whether it can be an alternative to didactic lectures in medical education. Our study aimed to evaluate the effectiveness of SBL versus traditional lectures in retention of knowledge. Methods A randomized controlled trial was conducted among medical students who were divided in two groups (36 students each). Each group received the same information about diagnosis and management of bronchial asthma, but with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(38 reference statements)
3
2
0
Order By: Relevance
“…The themes indicate that although each participant had undergone a unique experience based on their individual choices, they all had the same view-that the learning experience was more effective and enjoyable than that of their conventional class. Similar results were reported by Akselbo and Aune (2022) and Tawfik et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…The themes indicate that although each participant had undergone a unique experience based on their individual choices, they all had the same view-that the learning experience was more effective and enjoyable than that of their conventional class. Similar results were reported by Akselbo and Aune (2022) and Tawfik et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…However, the qualitative analysis revealed that the students perceived the high-fidelity simulation to reinforce their learning of pharmacology more than case-based tutorial sessions. Similar findings have been observed in a previously conducted randomized controlled trial which compared simulation-based learning to traditional lectures in teaching the diagnosis and management of bronchial asthma (43). Thus, it is worth considering both the modality’s effect on students’ performance and the students’ perception of the learning experiences in deciding whether or not to adapt it.…”
Section: Discussionsupporting
confidence: 87%
“…In alignment with previously conducted studies (4143), the quantitative analysis of the current study showed that the choice of modality did not affect the students’ knowledge retention. However, the qualitative analysis revealed that the students perceived the high-fidelity simulation to reinforce their learning of pharmacology more than case-based tutorial sessions.…”
Section: Discussionsupporting
confidence: 86%
“…As for the secondary outcomes of attitudes, there was potential nonresponse bias if the surveys were more likely to be completed by residents with stronger knowledge and/or more positive attitudes toward the intervention. [3][4][5]8,12,13,16,17,20 primer-6-12…”
Section: Discussionmentioning
confidence: 99%